2019
DOI: 10.1002/chem.201900279
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerization of PtII Complexes Containing Two Different Photochromic Chromophores: Boron Chromophore versus Dithienylethene Chromophore

Abstract: In order to examine competitive photoisomerization, a series of novel photochromic PtII molecules that contain both dithienylethene (DTE) and B(ppy)Mes2 units (ppy=2‐phenylpyridine, Mes=mesityl) were successfully synthesized and fully structurally characterized. Their photochromic properties were examined by UV/Vis, emission and NMR spectroscopy. It was found that the DTE unit in all three compounds is the preferred photoisomerization site, exhibiting reversible photochromism with irradiation. The B(ppy)Mes2 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Variable temperature emission experiments reveal that the regioisomer with the internal B-N bond showed temperature dependent structural dynamics which was supported by TD-DFT calculations. They 89 The same group also 90 synthesized and characterized Pt(II) complexes that contain dithienylethene (DTE) and B( ppy)Mes 2 as photochromic units (58)(59)(60). UV/Vis and NMR experiments showed that only DTE units of all the complexes undergo reversible photoisomerization under UV light irradiation.…”
Section: Nc-chelate B-n Coordinated Boron Compoundsmentioning
confidence: 99%
“…Variable temperature emission experiments reveal that the regioisomer with the internal B-N bond showed temperature dependent structural dynamics which was supported by TD-DFT calculations. They 89 The same group also 90 synthesized and characterized Pt(II) complexes that contain dithienylethene (DTE) and B( ppy)Mes 2 as photochromic units (58)(59)(60). UV/Vis and NMR experiments showed that only DTE units of all the complexes undergo reversible photoisomerization under UV light irradiation.…”
Section: Nc-chelate B-n Coordinated Boron Compoundsmentioning
confidence: 99%
“…Similarly, cyclometallation of the N^C ligands also quenched the photoisomerization process of the B(ppy)Mes2 chromophore [40]. Several other studies have been carried out to obtain an in-depth knowledge of such chromophores and more can be found in references [38,[41][42][43][44][45][46]. Through various structural modifications and analogues, it has been established that photoisomerization could also be extended to N^C-chelate in addition to the ppy systems [47].…”
Section: -Arylpyridine-derived N^c-chelatesmentioning
confidence: 99%
“…Similarly, cyclometallation of the NˆC ligands also quenched the photoisomerization process of the B(ppy)Mes 2 chromophore [40]. Several other studies have been carried out to obtain an in-depth knowledge of such chromophores and more can be found in references [38,[41][42][43][44][45][46]. In order to examine the competitive photoisomerization processes, Wang and coworkers [38] prepared a series of cis and trans Pt(II) acetylides containing two photochromic units; i.e., dithienylethene (DTE) and B(ppy)Mes2 (7a-c, Figure 5).…”
Section: -Arylpyridine-derived N^c-chelatesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that dithienylethene (DTE) is a class of fascinating organic compounds, showing photochromism due to light-irradiation-induced structural transition between open form and closed form (Scheme S1 †). 16 So far, some DTE-based Pt(II) complexes have been reported, in which various DTE ligands coordinate with Pt(II) ions through some functional groups such as alkynyl group, [17][18][19][20][21] pyridyl group, 22 1,10-phenanthroline unit, 23 2-(thiophen-2-yl)-pyridine moiety, 24 2-(2-pyridyl)imidazole moiety, 25 and 1,3-di(2-pyridyl)benzene unit. 26 Some complexes were found to exhibit phtochromism, and even signicant switching of either luminescence or nonlinear optical (NLO) property due to the open/closed isomerization of DTE unit.…”
Section: Introductionmentioning
confidence: 99%